2021
DOI: 10.1038/s41416-021-01354-5
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminosalicylic acid inhibits stem cell function in human adenoma-derived cells: implications for chemoprophylaxis in colorectal tumorigenesis

Abstract: Background Most colorectal cancers (CRC) arise sporadically from precursor lesions: colonic polyps. Polyp resection prevents progression to CRC. Risk of future polyps is proportional to the number and size of polyps detected at screening, allowing identification of high-risk individuals who may benefit from effective chemoprophylaxis. We aimed to investigate the potential of 5-aminosalicylic acid (5-ASA), a medication used in the treatment of ulcerative colitis, as a possible preventative agent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…It has been hypothesised that the chemopreventive properties of the main classes of drugs available for IBD treatment are due to their direct (anticarcinogenic mechanisms) and indirect activity (reducing inflammatory activity) [ 47 , 48 ]. The scientific community has recently questioned the risk of developing colorectal cancer in IBD patients after being treated with immunomodulator therapy.…”
Section: Selective and Targeted Ibd Therapies And Their Anticarcinoge...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesised that the chemopreventive properties of the main classes of drugs available for IBD treatment are due to their direct (anticarcinogenic mechanisms) and indirect activity (reducing inflammatory activity) [ 47 , 48 ]. The scientific community has recently questioned the risk of developing colorectal cancer in IBD patients after being treated with immunomodulator therapy.…”
Section: Selective and Targeted Ibd Therapies And Their Anticarcinoge...mentioning
confidence: 99%
“…In addition, 5-ASA also suppresses the Wnt/β-catenin pathway, which is an effective anticarcinogenic mechanism. Finally, it has also been found to induce a cell cycle stop or apoptosis in carcinomatous cells with deficient/mutated β-catenin or mutated COX-2 [ 47 ].…”
Section: Selective and Targeted Ibd Therapies And Their Anticarcinoge...mentioning
confidence: 99%
“…The 5-ASA antineoplastic mechanism of action in CRC is strongly related to suppressing the Wnt/β-catenin pathway [ 74 ]. Mutation of the suppressor gene adenomatous polyposis coli (APC) is a common cause of genetic changes leading to the development of colorectal cancer by nuclear accumulation of β-catenin.…”
Section: Mesalazine’s Anticancer Mechanisms Of Actionmentioning
confidence: 99%
“…β-catenin then translocates into the cell nucleus, where it activates the transcription factor TCF/LEF (T-cell factor/lymphocyte enhance factor), which increases cell proliferation by activating the transcription of target genes encoding proteins such as c-Myc, cyclin D1, and CD44 [ 75 , 79 ]. Mutations resulting in upregulated Wnt/β-catenin signaling have been demonstrated to be sufficient for early adenoma formation [ 74 , 80 ].…”
Section: Mesalazine’s Anticancer Mechanisms Of Actionmentioning
confidence: 99%
“…In the present study, the authors 1 provided, for the first time, consistent data on this issue and found no evidence for 5‐ASA reducing the weighted incidence of CRC in IBD patients on 5‐ASA versus those who had never used them. This is despite the potential protective effects of 5‐ASA from its intrinsic anti‐neoplastic properties on colon dysplasia seen in several studies in both UC and colonic CD 5 . So, to the question ‘is it time to systematically stop 5‐ASA when introducing biologics in IBD?’.…”
mentioning
confidence: 98%